2010
DOI: 10.1097/brs.0b013e3181bb5203
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-2 and Bone Marrow Aspirate With Allograft as Alternatives to Autograft in Instrumented Revision Posterolateral Lumbar Spinal Fusion

Abstract: rhBMP-2 may be an appropriate alternative to autogenous bone graft in both single- and multilevel revision PLF, whereas BMAA may be appropriate as a substitute in single-level revision PLF. The use of BMAA in single-level revisions may be a more cost-effective option than rhBMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…In the autograft group, Several studies also documented the use of BMP-2 in the spine, noting superior fusion rates for lumbar fusion when comparing BMP-2 and bone marrow aspirate with allograft as an alternative to auotograft. 39 Rogozinski et al 40 showed that BMP-2 is safe and effective in augmenting posterolateral lumbar spinal fusion when added to autograft. This study reported a healing rate of 100% in 16 patients.…”
Section: A B E1054mentioning
confidence: 99%
“…In the autograft group, Several studies also documented the use of BMP-2 in the spine, noting superior fusion rates for lumbar fusion when comparing BMP-2 and bone marrow aspirate with allograft as an alternative to auotograft. 39 Rogozinski et al 40 showed that BMP-2 is safe and effective in augmenting posterolateral lumbar spinal fusion when added to autograft. This study reported a healing rate of 100% in 16 patients.…”
Section: A B E1054mentioning
confidence: 99%
“…BMA supplementation of rhBMP-2 in a murine fusion model has a synergistic effect resulting in greater fusion mass than BMP alone (Rao et al, 2009). A clinical series reported a 100% union rate utilizing BMA with allograft in single level revision lumbar cases, equivalent to rhBMP-2 and autograft (Taghavi et al, 2010).…”
Section: Principles Of Bone Formation In Fusionmentioning
confidence: 98%
“…MSCs can be either autogenous or allogeneic, and are commonly found in bone marrow, periosteum, muscle, and adipose tissue. [36][37][38][39] In a prospective study, BMA and allograft were compared with both BMP and ICBG in single-level and 2-level revision posterolateral spinal fusions. 34 Bone marrow aspiration (BMA) of the vertebral body pedicle or the iliac crest can yield MSCs.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…25 Advantages of MSCs include ease of isolation and "ex vivo" expansion, which preserve their potential for plasticity and self-renewal. 39 Like DBM, BMA poses the challenge of substantial variability in processing. A study by Muschler et al 35 demonstrated osteogenic progenitor cell concentration of vertebral pedicle aspirates to be 71% higher than that of iliac crest.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%